PENGENDALIAN MANAJEMEN DENGAN ANGGARAN BIAYA OPERASIONAL PADA PT.ISIS INDONESIA CABANG MEDAN - Chainar Elly Ria (JURNAL GLOBAL MANAJEMEN, 2020)
This research aims to analyze the budget of operational cost and its realization at PT. ISS Indonesia Medan Branch. The population in this study is the operational budget realization data at PT. ISS Indonesia Medan Branch. The sample in this study is the financial realization report in the 2017-2019 period. The research method is descriptive qualitative and comparative methods. Data collection in this study was carried out in two ways, namely library research & field research. The analysis technique used in this method is analysis of variance to determine the difference between budget and realization. The conclusion is that the analysis of the variance of the operating budget with the realization is favorable. Company management has taken effective steps in terms of every operational cost of the company. It is recommended to PT. ISS Indonesia Medan Branch to pay more attention to operational costs so that it is more effective and efficient to achieve company goals.